1975
DOI: 10.1021/jm00241a013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor properties of new glycosides of daunomycinone and adriamycinone

Abstract: The synthesis of 4'-epi-daunorubicin and of 4'-epi-adriamycin was performed by condensation of 2,3,6-trideoxy-3-trifluoroacetamido-4-O-trifluoroacetyl-alpha-L-arabino-hexopyranosyl chloride with daunomycinone or the protected adriamycinone derivative 17, respectively. Both the alpha and beta anomers were obtained and characterized. All new compounds are biologically active in cultured cells and the alpha anomers display noticeable activity in experimental tumors in mice. Interestingly, 4'-epi-adriamycin (4) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(49 citation statements)
references
References 2 publications
(4 reference statements)
0
48
1
Order By: Relevance
“…Studies on the structure-activity relationships have indicated that some structural features of these antitumour antibiotics are important determinants for their binding to DNA. It has been shown (Arcamone et al, 1975;Zunino et al, 1972) that modifications in the amino sugar moiety, as well as in the aglycone moiety can change the ability of these molecules to bind to DNA and eventually their biological properties.…”
mentioning
confidence: 99%
“…Studies on the structure-activity relationships have indicated that some structural features of these antitumour antibiotics are important determinants for their binding to DNA. It has been shown (Arcamone et al, 1975;Zunino et al, 1972) that modifications in the amino sugar moiety, as well as in the aglycone moiety can change the ability of these molecules to bind to DNA and eventually their biological properties.…”
mentioning
confidence: 99%
“…Many anlinosugars and related antibiotics interfere with protein synthesis (7) and their bacterial toxicities could be greatly modified by manipulating the stereocheinistry or re~noving o111y one hydroxyl group in the niolecule (8). Furthermore, the reported reduced toxicity to cultured heart cells of 4'-epiadriamycin (9) pointed to the importance of the aminosugar 4-deoxydaunosamine (7) in attempts to reduce cardiotoxicity of this group of drugs.…”
Section: Common Vet Very Undesirable Side Effects Is Theirmentioning
confidence: 99%
“…Intensive and promising efforts are currently directed in several laboratories towards the development of semisynthetic, modified analogs of daunorubicin and adriamycin which might display increased efficacy or lower cardiopathogenicity, a cumulative, dose-related side-effect (3) that curtails the administration of the natural drugs. To this end, a large variety of analogs modified in the sugar portion have been synthesized and, in part, evaluated pharmacologically (4)(5)(6)(7)(8)(9)(10). Among the substitutes for daunosamine whose attachment to…”
mentioning
confidence: 99%
“…4-Deoxy-N-trifluoroacetyldaunosamine (13) has been prepared previously in a four-step reaction sequence from methyl N-trifluoroacetyldaunosaminide which, in turn, had been elaborated from natural daunorubicin (5,6 15 R = Me, X = picrate 11 R = E t , X = CI 16 R = E t , X = CI daunosamine for which there is now available a practical method of preparation starting from methyl a-D-mannopyranoside and comprising 9 steps (14). A multistep, achiral synthesis of racemic, 4-deoxy-D,L-daunosamine has also been achieved (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation